Spatiotemporal Controls on the Delivery of Dissolved Organic Matter to Streams Following a Wildfire. Issue 16 (26th August 2022) - Roebuck, Jesse Alan; Bladon, Kevin D.; Donahue, David; Graham, Emily B.; Grieger, Samantha; Morgenstern, Karl; Norwood, Matthew J.; Wampler, Katie A.; Erkert, Lisa; Renteria, Lupita; Danczak, Robert; Fricke, Susan; et al.
Abstract: Warmer and drier climate has contributed to increased occurrence of large, high severity wildfires in the Pacific Northwest, drawing concerns for water quality and ecosystem recovery. While nutrient fluxes generally increase post‐fire, the composition of organic matter (OM) transported to streams immediately following a fire is poorly constrained, yet can play an integral role in downstream water quality and biogeochemistry. Here, we quantified the spatiotemporal patterns of dissolved OM (DOM) chemistry for five streams burned by wildfires in Oregon, USA in 2020. We sampled over a 24 hr storm event 1 month after the fire revealing DOM dynamics were temporally variable, but spatially linked with burn severity. Specifically, nitrogen and aromatic character of DOM increased in streams burned at greater severity. Our results suggest spatially distinct gradients of burn severity impact DOM dynamics immediately following fire activity and highlight a key gap in our knowledge of post‐fire DOM transport to streams. Plain Language Summary: Wildfires are increasing in frequency and intensity in the Pacific Northwest. Following a wildfire, rain events can mobilize large amounts of charred material from the ground and transport to local water bodies, thus leaving major concerns for how changes in wildfires will impact local water quality. Our study aimed to understand how the water quality of small streams that have been impacted by varying degrees of burn severity responds to major storm events immediately following a wildfire. To achieve this objective, we collected water samples throughout a storm event for 24 hrs in 1 hr intervals from five streams impacted by the 2020 Holiday Farm Fire in Oregon, USA. We found differences in the dissolved materials that were delivered to the streams that was directly related to how severe the fire burned. These results will help improve our understanding of how streams respond to wildfire activity and be able to predict how more frequent and intense fires impact local water quality. Key Points: Dissolved organic carbon concentrations in stream water were driven by local hydrology during the first post‐fire storm event Burn severity was a primary control on dissolved organic matter composition delivered to streams Spatial variation in dissolved organic matter composition in streams overprinted hydrological controls